Environmental isues of mining activities in Tay Nguyen - Xuan, Pham Tich; Anh, Tran Tuan; Tra, Doan Thi Thu; Nga, Hoang Thi Tuyet; Dang, Pham Thanh; Lien, Nguyen Thi; Pho, Nguyen Van (Vietnam Journal of Earth Sciences, 2015)
Intensive mining activities, specially illegal, negatively affect environment in Tay Nguyen. Mining of gold and tin placers, sand and pebble disturbed the landscape, changed river bed caussing river bank erosion. Exploited wastes from mine, for example, kaolin mine in Loc Chau (Lam Dong province) destroyed and retrograded tea land. There observed evidences of acid mine drainage and pollution of heavy metal including Cu, Pb, Hg, et.c in surface water, stream sediments and soils from some gold mines such as Dak Ripen (Kon Tum), Krong A (Dak Lak) and Tra Nang (Lam Dong). Main causes of mining environmental problems are failure of management, so the first and most important measure of mitigation is to improve the management of mining activities. References Borisenko A.S., Trần Trọng Hòa, V.I. Vasilev, N.K. Morsev, Vũ Văn Vấn, Ngô Thị Phượng, Hoàng Hữu Thành, Trần Tuấn Anh, Phạm Thị Dung, 2008: Phát hiện lần đầu tiên khoáng vật Jonassonite - AuBi5S4 ở Việt Nam. Tạp chí Các Khoa học về Trái Đất, T.30, (3), tr.193-198. Damigos D., 2006: An overview of environmental valuation methods for the mining industry. Journal of Cleaner Production, Volume 14, Issues 3-4, P. 234-247 Dixon-Hardy, D.W.& Engels, J.M., 2007: Guidelines and Recommendations for the Safe Operation of Tailings Management Facilities. - Environmental Engineering Science, 24 (5), 14-26. Doolittle, J.J., Frisbee, N.M. and Hossner, L.R., 1992: Evaluation of acid-base accounting techniques used in surface-mine reclamation, Proc. 1992 Meeting of the American Society of Surface Mining and Reclamation, 14-18 June, Duluth, MN, p68-76. Trần Trọng Hòa, Ngô Thi Phượng, Borisenko A.S., Izokh A.E., Vũ Văn Vấn, Bùi Ấn Niên, Trần Tuấn Anh, Phạm Thị Dung, 2005: Đặc điểm địa hóa-đồng vị của quặng hóa vàng Mesozoi sớm và Mesozoi muộn trong mối liên quan với hoạt động magma rìa Đông Nam địa khối Đông Dương. Tạp chí Địa chất, Loạt A, số 295, tr.15-24. Nguyễn Kim Hoàng, Nguyễn Văn Mài, 2010: Đặc điểm khoáng hóa và triển vọng vàng gốc Trà Năng, tỉnh Lâm Đồng. Đại học Quốc gia Tp. HCM. Nilsson J-A, Randhem J., 2008: Environmental Impacts and Health Aspects in the Mining Industry. Department of Energy and Environment. Division of Environmental Systems Analysis. Chambers University of Technology. Göteborg, Sweden, 2008. publications.lib.chalmers.se/records/fulltext/85984.pdf‎ Plumlee, G.S. and Nash, J.T., 1995: Geoenvironmental models of mineral deposits–fundamentals and applications. U.S. Geol. Survey Open-File Report 95-831, p.1-18. Lê Văn Thành, 2004: Khai thác khoáng sản và tác động đến môi trường. Địa chất, N.281 Vũ Văn Vấn, Trần Trọng Hòa, A.S. Borisenko, Ngô Thị Phượng, Trần Tuấn Anh, Trần Hồng Lam, Đặng Trung Thuận, Phạm Thị Dung, 2007: Quặng hóa vàng Tà Năng, đới cấu trúc Đà Lạt: Điều kiện hình thành và bối cảnh địa động lực. Tạp chí Các Khoa học về Trái Đất, T.29, (2), tr.154-160. Báo cáo hiện trạng môi trường tỉnh Lâm Đồng giai đoạn 2006 - 2010: Sở Tài nguyên và Môi trường Lâm Đồng. http://www.lamdong.gov.vn/vi-VN/a/sotnmt/du-lieu-so/moi-truong/Pages/baocaohientrang2006-2010.aspx. Guidebook for Evaluating Mining Project EIAs, 2010: www.elaw.org/files/mining-eia-guidebook/Chapter1.pdf Global Acid Rock Drainage Guide (http://www.gardguide.com/index.php/Main_Page) UNEP, 1997: Industry and environment, mining and sustainable development. http://www.uneptie.org/vol20no4.htmO; 1997.